Economic Growth as a Moderator in the Nexus between Public Finance, Human Development, and Income Inequality in Aceh - Royanti, Mella; Nasir, Muhammad; Seftarita, Chenny (Grimsa Journal of Business and Economics Studies, 2025)
Income inequality continues to pose a significant economic challenge in Indonesia, particularly at the regional level. Although economic growth is regarded as a pathway to improved public welfare, it can either alleviate or exacerbate existing income disparities. This study investigates the moderating role of economic growth in the relationship between public finance, human development, and income inequality, using panel data from 23 districts and cities in Aceh Province over the period 2017-2023. Employing panel data regression with the Moderated Regression Analysis (MRA) technique, the analysis focuses on three key independent variables: local tax revenue, village funds, and the Human Development Index (HDI). The results show that local tax revenue is positively associated with income inequality, while village funds have no statistically significant effect. The HDI, on the other hand, is significantly and negatively associated with inequality. However, economic growth does not moderate the effects of local tax revenue or village funds on income inequality. Notably, it does moderate the relationship between HDI and inequality, with the effect of HDI turning positive when interacted with economic growth. These findings highlight the need for local governments to prioritize inclusive development through strengthened fiscal management, more targeted village fund allocations, and sustained investment in human capital.